Percutaneous sensitization is limited by in situ inhibition of cutaneous dendritic cell migration through skin-resident regulatory T cells - Hanakawa, Sho; Kitoh, Akihiko; Shibuya, Rintaro; Dainichi, Teruki; Nomura, Takashi; Honda, Tetsuya; Egawa, Gyohei; Otsuka, Atsushi; Nakajima, Saeko; Fujita, Mitsugu; Kabashima, Kenji (Journal of allergy and clinical immunology, 2019)
Percutaneous sensitization is associated with various allergic diseases, including asthma and food allergies. However, the immunologic mechanisms underlying how the skin regulates percutaneous sensitization are still unclear. We aimed to investigate whether and how CD4+Foxp3+ regulatory T (Treg) cells residing in the skin regulate percutaneous sensitization in the skin. Selective reduction of numbers of cutaneous Treg cells was achieved by means of intradermal injection of diphtheria toxin into the ear skin of Foxp3DTR mice, in which Treg cells specifically express the diphtheria toxin receptor fused with green fluorescent protein. Thirty percent to 40% of cutaneous Treg cells were capable of IL-10 production in both mice and human subjects. Selective reduction of cutaneous Treg cells at the sensitization site promoted migration of antigen-bearing dendritic cells (DCs) to the draining lymph nodes (dLNs). Accordingly, sensitization through the skin with reduced numbers of Treg cells led to enhanced antigen-specific immune responses in the dLNs, including both effector T-cell differentiation and T cell–dependent B-cell responses, such as the development of germinal center B cells expressing IgG1 and IgE. Furthermore, antigen-bearing cutaneous DC migration was enhanced in mice with IL-10 deficiency restricted to the cutaneous Treg cell compartment, suggesting an important role of cutaneous IL-10+ Treg cells in limiting percutaneous sensitization. Treg cells with a skin-homing phenotype in skin dLNs expressed high levels of IL-10, suggesting that they contribute to renewal and maintenance of the cutaneous IL-10+ Treg cell population. Skin-resident Treg cells limit percutaneous sensitization by suppressing antigen-bearing DC migration through in situ IL-10 production. [Display omitted]